Avaliação de desempenho do Self-Reporting Questionnaire como instrumento de rastreamento psiquiátrico: um estudo comparativo com o Structured Clinical Interview for DSM-IV-TR Performance of the Self-Reporting Questionnaire as a psychiatric screening questionnaire: a comparativestudy with Structured Clinical Interview for DSM-IV-TR - Daniel Maffasioli Gonçalves; Airton Tetelbon Stein; Flavio Kapczinski (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2008)
O SRQ (Self-Reporting Questionnaire) é um instrumento de rastreamento psiquiátrico originalmente composto por 30 itens. A versão brasileira do SRQ-20 (versão com as 20 questões para rastreamento de transtornos mentais não-psicóticos) foi validada no início da década de 1980. O objetivo deste estudo foi validar a versão brasileira do SRQ-20 e dos cinco itens de rastreamento de transtorno por uso de álcool oriundos do SRQ-30, comparando com entrevista psiquiátrica usando SCID-IV-TR (Structured Clinical Interview for DSM-IV-TR) como padrão-ouro. O estudo foi conduzido em Santa Cruz do Sul, Rio Grande do Sul, Brasil, com 485 indivíduos (54,8% mulheres, idade média 40,04). Os 5 itens de rastreamento de transtornos por uso de álcool mostraram sensibilidade baixa (66%). O SRQ-20 apresentou como ponto de corte ideal 7/8, com sensibilidade de 86,33% e especificidade de 89,31%. O poder discriminante para diagnóstico psiquiátrico do SRQ-20 foi 0,91. O coeficiente Cronbach alfa foi 0,86. The SRQ (Self-Reporting Questionnaire) is a psychiatric screening tool that originally included 30 questions. The Brazilian version of SRQ-20 (a version that includes the 20 items for non-psychotic mental disorders) was validated in the early 1980s. The objective of the present study was to validate the Brazilian version of SRQ-20 and the 5 items for alcohol-related disorders as compared to the SCID-IV-TR (Structured Clinical Interview for DSM-IV-TR) as the gold standard. The study was conducted in Santa Cruz do Sul, a small town in southern Brazil, with 485 subjects (54.8% females, mean age 40.04 years). The 5 items for alcohol-related disorders showed low sensitivity (66%). The optimum cutoff value for SRQ-20 was 7/8, with 86.33% sensitivity and 89.31% specificity. The discriminant power of SRQ-20 for psychiatric screening was 0.9, and Cronbach's alpha was 0.86.